Epidemiology, risk factors and impact on long‐term pancreatic function of infection following pancreas‐kidney transplantation. (11th March 2013) - Herrero‐Martínez, J. M.; Lumbreras, C.; Manrique, A.; San‐Juan, R.; García‐Reyne, A.; López‐Medrano, F.; Lizasoain, M.; de, B.; Andrés, A.; Jiménez, C.; Gutiérrez, E.; Moreno, E.; et al.
Abstract Limited information exists about epidemiology and risk factors of infection following pancreas‐kidney transplantation and its impact on long‐term pancreatic graft function. A retrospective chart review of episodes of severe infection in consecutive pancreas‐kidney transplantations in a single institution was performed to assess the epidemiology, risk factors for infection and their impact on the development of pancreatic graft dysfunction. Ninety‐four (81%) of 116 recipients (median follow‐up of 1492 days; mean 1594) developed 248 episodes of severe infection. Bacterial infections were present in 208 episodes, with 12% of the isolates resistant to antibiotics used in prophylaxis. There were 40 episodes of fungal infection in 32 patients (28%) (mostly Candida spp), and CMV disease appeared in 20 patients (17%), of which 50% appeared after the third month following surgery. The multivariate analysis identified that surgical re‐intervention and the use of steroid pulses were independently associated with the development of any infection. Additionally, pre‐transplant evidence of peripheral artery disease, a longer cold ischaemia time and high transfusional requirements were associated with fungal infections. Cytomegalovirus (CMV) mismatch was independently related to CMV disease and female sex, and bladder drainage of the exocrine pancreas was associated with urinary tract infection. At the end of follow‐up, 29 patients (25%) had developed severe pancreatic graft dysfunction, and fungal infection was independently associated with it. Our study identifies a subset of pancreas‐kidney transplant recipients at a higher risk of developing severe infection. Fungal infection is an independent risk factor for the development of severe pancreatic graft dysfunction.